Evaluation of the angiographic outcomes after clipping of intracranial aneurysms: determination of predisposing factors for occurrence of aneurysm remnants. (2nd April 2020) - Kim, Jung-Jae; Cho, Kwang-Chun; Suh, Sang Hyun; Chung, Joonho; Jang, Chang Ki; Joo, Jin-Yang; Kim, Yong Bae
ABSTRACT: Objectives : Aneurysm remnants after microsurgical clipping have a risk of regrowth and rupture and have not been validated in the era of three-dimensional angiography. Therefore, this study aimed to evaluate the angiographic outcome using three-dimensional rotational images and determine the predictors for remnants after microsurgical clipping. Methods : Between January 2014 and May 2017, 139 aneurysms in 106 patients who were treated with microsurgical clipping, were eligible for this study. For the determination of aneurysm remnants after microsurgical clipping, the angiographic outcomes were evaluated using follow-up digital subtraction angiography within 7 days for unruptured aneurysms or within 2 weeks for ruptured aneurysms. According to the Sindou classification, the aneurysm remnants were dichotomized, and subgroup analysis was performed to identify the predictors of aneurysm remnants after clipping with various imaging parameters and clinical information. Results : The overall rate of aneurysm remnants was 29.5% (41/139), in which retreatments were needed in 6.5% (9/139). The neck size and maximum diameter of aneurysms were independent predisposing factors for the aneurysm remnants that need retreatment (OR: 2.30; p < 0.001; OR: 1.38; p < 0.001, respectively). Conclusions : This study demonstrated a low incidence of aneurysm remnants after microsurgical clipping which need to retreatment. However, selective postoperative angiography could provide us clear information of surgical result and evidence for long-term follow-up for some aneurysms with larger neck size (>5.7 mm) and maximum diameter (>7.1 mm).